Student satisfaction survey at XYZ Campus using the Slovin formula method and mwater application - Nurkholis; Pria Sukamto; Fia Dhatul Prima Kusuma (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
The progress of an institution as a learning process organizer on a campus is a key organizational goal, as it fosters competitiveness and enhances benefits for the organizatio. However, in the process of achieving this progress, it is necessary to measure student satisfaction, whether they are satisfied or not, which is the problem in this study. The purpose of this study is to measure student satisfaction with each campus resource that has been provided, whether it has reached the expected student satisfaction category or not. The method used to measuring this satisfaction is the Slovin method and the MWater application, which method is a method for collecting data and opinions from customers or students regarding the products or services received. In this case, a student satisfaction survey can be used to determine the level of student satisfaction and interest in services and facilities on campus. This student satisfaction survey can be packaged in the form of questions related to new student services, such as information regarding new student admissions (PMB), administrative services and available campus facilities. With the MWater application, we can create survey forms and collect survey answers quickly and efficiently, while the Slovin formula is used to determine the number of samples needed from the population of the number of new students in each faculty. The results of the study using the Slovin formula and the Mwater application showed that 77.8% of students were satisfied with the campus service, while 5.6% were dissatisfied, 5.6% were dissatisfied, and 11.1% were very satisfied. The results of this survey can then be used as a reference for the campus in planning future promotional strategies and university policies.